2018
DOI: 10.5897/ajmr2018.8984
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility patterns of uropathogenic microorganisms associated with vesico-vaginal fistula (VVF) patients in Abakaliki, South eastern Nigeria

Abstract: The objective of this study was to review the antimicrobial susceptibility patterns of uropathogenic microorganisms associated with VVF patients in Abakaliki, South eastern Nigeria. Out of the 117 bacterial isolates obtained from 108 mid-stream urine samples of VVF patients, 72 isolates [15 (20.8%) Staphylococcus aureus, 8 (11.1%) Enterococcus faecalis, 12 (16.7%) Klebsiella pneumoniae, 11 (15.3%) Proteus mirabilis, and 26 (36.1%) Escherichia coli] were obtained from pre-surgery VVF patients, while 45 isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The highest resistance pattern, reaching more than 70%, was found in the antibiotics tetracycline, amoxicillin, and cotrimoxazole, while the sensitivity pattern reached up to 100% in imipenem antibiotics. 3 Thus, in our study, antibiotics that could be considered for urinary tract infections caused by gram-negative bacterial infections in vesicovaginal fistula patients were aztreonam, ertapenem, and meropenem, with susceptibility…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The highest resistance pattern, reaching more than 70%, was found in the antibiotics tetracycline, amoxicillin, and cotrimoxazole, while the sensitivity pattern reached up to 100% in imipenem antibiotics. 3 Thus, in our study, antibiotics that could be considered for urinary tract infections caused by gram-negative bacterial infections in vesicovaginal fistula patients were aztreonam, ertapenem, and meropenem, with susceptibility…”
Section: Discussionmentioning
confidence: 70%
“…16 In contrast, four previous studies, including research by Ugbo et al showed a high sensitivity pattern found in the antibiotics gentamicin, ciprofloxacin, nitrofurantoin, ofloxacin, and imipenem. 3 Research by Dereje et al (2017), a pattern of high sensitivity was found for the antibiotics amoxicillin and ciprofloxacin. 14 Research by Marami et al (2022), a pattern of high sensitivity was found for the antibiotics penicillin and cefoxitin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation